Polymeric Gene Carriers Bearing Pendant β‐Cyclodextrin: The Relevance of Glycoside Permethylation on the "In Vitro" Cell Response. Issue 7 (2nd February 2016) - Redondo, Juan Alfonso; Martínez‐Campos, Enrique; Plet, Laetitia; Pérez‐Perrino, Mónica; Navarro, Rodrigo; Corrales, Guillermo; Pandit, Abhay; Reinecke, Helmut; Gallardo, Alberto; López‐Lacomba, José Luis; Fernández‐Mayoralas, Alfonso; Elvira, Carlos
Abstract : The incorporation of cyclodextrins (CDs) to nonviral cationic polymer vectors is very attractive due to recent studies that report a clear improvement of their cytocompatibility and transfection efficiency. However, a systematic study on the influence of the CD derivatization is still lacking. In this work, the relevance of β‐CD permethylation has been addressed by preparing and evaluating two series of copolymers of the cationic N ‐ethyl pyrrolidine methacrylamide (EPA) and styrenic units bearing pendant hydroxylated and permethylated β‐CDs (HCDSt and MeCDSt, respectively). For both cell lines, CDs permethylation shows a strong influence on plasmid DNA complexation, "in vitro" cytocompatibility and transfection efficiency of the resulting copolymers over two murine cell lines. While the incorporation of the hydroxylated CD moiety increased the cytotoxicity of the copolymers in comparison with their homopolycationic counterpart, the permethylated copolymers have shown full cytocompatibility as well as superior transfection efficiency than the controls. This behavior has been related to the different chemical nature of both units and tentatively to a different distribution of units along the polymeric chains. Cellular internalization analysis with fluorescent copolymers supports this behavior. Abstract : Permethylation of pendant β ‐cyclodextrin (CD) in linear cationic copolymers has been shown to strongly influence the interaction with DNA and the "in vitro" performance of polymer/DNA complexes as nonviral gene carriers, as compared to hydroxylated CD and cationic controls. While hydroxylated moieties increase cytotoxicity with respect to control, permethylated structures lead to more cytocompatible polymers, exhibiting good transfection efficiencies.